Relationship between Farm Scale and Broilers Farmers Income based on the Partnership system in Maros Regency - A. R. Siregar; S. N. Sirajuddin; R. Ranggadatu (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2014)
The study aimed to determine the relationship between scale of business and income of broiler breeders involved in partnerships. This study was carried out from April to December 2013 in Maros Regency, South Sulawesi Province. This research was descriptive quantitative using primary and secondary data obtained through observation and interviews. The population of the study was all the breeders who involved in partnership in Maros Regency, totaling 73 breeders. Forty two samples were withdrawn from the population and were grouped according to the business scale, namely <3500 birds, 3500-6500 birds, and > 6500 birds per farmer, respectively. Data were analyzed descriptively using the formula π = TR - TC , in which π = Net income (IDR/period). Results of study showed that the scale of business did not affect the income of broiler breeders who do partnerships. To increase the income of farmers, the partner company should pay attention to other factors rather than just the besides scale of the broiler farmers.